PERKEMBANGAN TEKNOLOGI MENGHARUSKAN PEKERJA UNTUK MEMILIKI KETERAMPILAN BARU YANG RELEVAN - Dhanes Danarjati Soepono; Adelina Siregar, Rospita; Siringoringo, Poltak (Honeste Vivere, 2025)
Rapid technological developments, especially in the context of the Industrial Revolution 4.0, have changed the world of work significantly and require workers to master new and relevant skills. This article analyzes the impact of technological developments on the need to increase workers' skills, especially in relation to social security and work safety laws in Indonesia. The aim of this research is to explore how changing skills requirements affect occupational safety and social protection of workers under the applicable legal framework. By reviewing regulations such as Law no. 40 of 2004 concerning the National Social Security System and Law no. 1 of 1970 concerning Occupational Safety, this research highlights the legal responsibility of companies in ensuring workers have the ability to work safely using new technology. The methodology used includes legal studies as well as case studies from the manufacturing and mining sectors, which have been greatly impacted by technology. The results show that a lack of relevant skills increases the risk of work accidents and can affect workers' social security claims. Therefore, continuous skills development is critical to bridge this gap and ensure worker safety and regulatory compliance.